(untitled) (Eurasian Journal of Philology Science and Education, 2015)
In this scientific article the morphological methods for forming names of complex diseases that relate to a person were discussed. Also it was described that in the Kazakh language names of diseases are formed by the addition of two or more words . Related to this there were given specific examples. In the Kazakh language , there are several ways to form the name of various diseases. This article describes a uniform system and the structure of these names and peculiar model of word formation. In Kazakh language vocabulary as part of lexical items parts of speech such as noun + noun , adjective + adjective , noun + verb , verb + verb + pronoun pronoun , adjective + noun are used. Complicated diseases names formed in this way are considered as part of a several big lexical groups. There are the following features of the formation of words in the complex diseases’ names; firstly, the names of components in interconnected by valency secondly, designation of disease names based on the meaning, semantic boundary and sound combination of words.